Utilization of Bio Slurry with Input of Buffalo Faeces and Water Hyacinth (Eichornia crassipes) With Various Doses of MOD (Microorganism Decomposer) on Productivity of Kelor (Moringa oleifera) in Samosir - Samuel Pito Rando; Nurzainah Ginting; Tri Hesti Wahyuni; Armyn Hakim Daulay; Yunilas . (Universitas Sumatera Utara, 2017)
Abstract.This study aims to determine effects of utilization of Bio-Gas Slurry With buffalo Feces Input And water hyacinthwith Various Dosage MOD (Microorganisme Decomposer) on Productivity of Moringa oleifera. Research conducted at the field experimental, Samosir Sumatra Utara in April-November 2017. The design used in the study was split plot design with four replications. First factor (M): dosage decomposer, M1= 1 liters/150 kg and M2= 2 liters/150 kg. Second factor (P): dosage was fertilizier of Bio-Gas Slurry With buffalo Feces Input And water hyacinth(ton/ha/year), P0=0, P1=20, P2=40. The variable were plant height, stem diameter and number of branches. The results showed that dosage decomposer and dosage of fertilizer Bio-Gas Slurry significantly affectplant height, stem diameter and number of branches Moringaoleifera.The utilization of Bio-Gas With buffalo Feces Input And water hyacinthwith Various Dosage MOD affect plant height, stem diameter and number of branches. It is concluded that dosage 2 liter/150 kg and application 40 ton/ha/year show higher on production of Moringa oleifera. Keyword: Bio-Gas Slurry, Buffalo faeces, Water Hyacinth, Productivity, Moringa oleifera